Influência do movimento recíproco na resistência à torção dos instrumentos de NiTi: reciproc, waveone e protaper universal - Rafael Rodrigues Soares de Magalhaes (2014)
The mechanical properties of the endodontic instruments are affected by factors such as diameter, design, chemical composition and thermo-mechanical treatments applied during the manufacturing process. The main goal of this study was to assess the flexibility and torsional resistance of the NiTi Reciproc (RC), Wave One (WO) and ProTaper Universal (PTU) instruments, new and after clinical use. The instruments chemical composition was analyzed with X-Ray energy spectroscopy (EDS), the present phases were determined by X-Ray Diffractions (DRX) and the transformation temperatures were obtained with differential scanning calorimeter (DSC). Images from the longitudinal and transversal sections were used for determining the diameter and the area at 3mm from the tip (D3 and A3), the position where the mechanical requests are focused in clinical use and where the instruments are apprehended during the tests. The mechanical behavior has been evaluated through simulation of bending and torsion until rupture according to ISO 3630-1. The RC, WO and PTU instruments have presented a similar chemical composition with the predominance of phase at room temperature. However, Reciproc and Waveone instruments showed a significant increase in transformation temperatures, suggesting the presence of B19 phase, coexisting with the austenitic phase Despite showing similar D3, statistical analysis of the values of A3 between pairs of instruments analyzed showed significantly lower difference for RC instruments. The RC instruments were significantly more flexible, possibly due to the thermomechanical treatment applied to the wire (M-Wire) used in their manufacture process in addition to their cross section design, followed by WO instruments, which are also made of M-Wire, and PTU instruments, in that order. Among the new instruments, PTU showed significantly lower maximum torque values in torsion tests. PTU instruments presented the highest angular deflection values, followed by RC and WO instruments, in that order. All systems reduced their torsional strength after clinical use. However, statistical comparison between the maximum torque values for new and after clinical use instruments, showed no statistically significant difference for any of the evaluated systems. Regarding the angular deflection, the comparison between new and after clinical use instruments demonstrated a reduction of the values of this parameter after clinical use, with the exception of RC instruments. However, statistical analysis showed no significant differences between the pairs of instruments analyzed. Key-words: NiTi instruments, Flexibility, Torsional resistance, Reciproc